Implementasi Metode Design Thinking Untuk Validasi Ide Startup Find Dosen - Wachid, Fadilah Alfan; sagirani, tri; wulandari, sri hariani eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
The COVID-19 pandemic has had an impact on various aspects of life, also has an impact on education. The Government has replaced the learning system, which should have been face-to-face directly to online. It makes students difficult to digest the information conveyed by the lecturer. With online learning, students find it difficult to find out the lecturer's busy schedule, and find it difficult to find the right time to contact the lecturer. Based on these problems, the author proposes a solution in the form of a startup find lecturer idea, this startup idea requires validation from the user to find out whether this startup is feasible or not. This startup find lecturer idea can provide facilities that can make it easier for students to contact lecturers. There are features for students who are undergoing final assignments, practical work, communication with guardian lecturers, lecturer schedules, announcement boards and status, as well as a list of lecturers for other purposes such as the interests of campus organizations. The validation of the startup idea of finding lecturers is carried out using the design thinking method and testing is carried out using the Usability Scale System. The display of the prototype presented as a result of the idea created has been tested on dynamic university students, resulting in an average System Usability Scale (SUS) score of 79.9 which means that the prototype containing the startup idea is acceptable with a percentile range of 85-95.